Retailing Distribution in Comparative Marketing: A Review - حودانة, بن عيسى (Dirasat in Economics and Business, 1981)
One of the expanding frontiers of marketing thought today is the comparative study of marketing systems and practices of variou nations. This area of study has been stimulated by the growing expansion of the overseas activities of various companies, throughout the world, and recently, extended by academic interest. This paper is mainly concerned with reviewing selected articles published in the area of comparative retailing systems of the emerging nations. It is further emphasised in this paper that marketing institutions and their related practices reflect the SocioEconomic environment in which they operate. Consequently, the adaptation of various marketing institutions and techniques from a developed to a less developed nation would require considerable time and adjustment.